A comprehensive survey on modeling of cyber‐physical systems. (18th October 2018) - Graja, Imen; Kallel, Slim; Guermouche, Nawal; Cheikhrouhou, Saoussen; Hadj Kacem, Ahmed
Summary: Modeling Cyber‐physical systems (CPS) is a challenging step that requires a lot of background from both the cyber and physical fields. However, there is a lack of studies in the existing literature that discuss the state of the art in modeling CPS or explore the research gaps in this area. In this paper, we survey existing approaches to modeling CPS. We focus on studying the considered CPS properties. Based on this study, we classify these properties and discuss their importance in different application domains. Moreover, research directions are presented to address key challenges in the specification of CPS models.